The end of American labor unions: the right-to-work movement and the erosion of collective bargaining - Hogler, Raymond L. (Westport, Conn., 2015)
"By examining the history of the legal regulation of union actions, this fascinating book offers a new interpretation of American labor-law policy―and its harmful impact on workers today.